The lethal internal face of the coronaviruses: Kidney tropism of the SARS, MERS, and COVID19 viruses. Issue 8 (30th June 2021) - Motavalli, Roza; Abdelbasset, Walid Kamal; Rahman, Heshu Sulaiman; Achmad, Muhammad Harun; Sergeevna, Nataliya Klunko; Zekiy, Angelina Olegovna; Adili, Ali; Khiavi, Farhad Motavalli; Marofi, Faroogh; Yousefi, Mehdi; Ghoreishizadeh, Shadi; Shomali, Navid; et al.
Abstract: The kidney is one of the main targets attacked by viruses in patients with a coronavirus infection. Until now, SARS‐CoV‐2 has been identified as the seventh member of the coronavirus family capable of infecting humans. In the past two decades, humankind has experienced outbreaks triggered by two other extremely infective members of the coronavirus family; the MERS‐CoV and the SARS‐CoV. According to several investigations, SARS‐CoV causes proteinuria and renal impairment or failure. The SARS‐CoV was identified in the distal convoluted tubules of the kidney of infected patients. Also, renal dysfunction was observed in numerous cases of MERS‐CoV infection. And recently, during the 2019‐nCoV pandemic, it was found that the novel coronavirus not only induces acute respiratory distress syndrome (ARDS) but also can induce damages in various organs including the liver, heart, and kidney. The kidney tissue and its cells are targeted massively by the coronaviruses due to the abundant presence of ACE2 and Dpp4 receptors on kidney cells. These receptors are characterized as the main route of coronavirus entry to the victim cells. Renal failure due to massive viral invasion can lead to undesirable complications and enhanced mortality rate, thus more attention should be paid to the pathology of coronaviruses in the kidney. Here, we have provided the most recent knowledge on the coronaviruses (SARS, MERS, and COVID19) pathology and the mechanisms of their impact on the kidney tissue and functions.